2015
DOI: 10.1186/s12936-015-0842-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of an automated capillary system for Plasmodium vivax microsatellite genotyping

Abstract: BackgroundSeveral platforms have been used to generate the primary data for microsatellite analysis of malaria parasite genotypes. Each has relative advantages but share a limitation of being time- and cost-intensive. A commercially available automated capillary gel cartridge system was assessed in the microsatellite analysis of Plasmodium vivax diversity in the Peruvian Amazon.MethodsThe reproducibility and accuracy of a commercially-available automated capillary system, QIAxcel, was assessed using a sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
2
3
0
1
Order By: Relevance
“…In this study, we initially tested four previously reported polymorphic microsatellite markers; however, based on sequencing analysis, one of them, TS_SSR32, was found to be monomorphic. This finding reinforces conceptions about the lack of precision in the automated capillary system to identify size polymorphisms, as also reported by Manrique et al [ 44 ]. Therefore, we evaluated the genotype of cysts using three microsatellite markers.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we initially tested four previously reported polymorphic microsatellite markers; however, based on sequencing analysis, one of them, TS_SSR32, was found to be monomorphic. This finding reinforces conceptions about the lack of precision in the automated capillary system to identify size polymorphisms, as also reported by Manrique et al [ 44 ]. Therefore, we evaluated the genotype of cysts using three microsatellite markers.…”
Section: Discussionsupporting
confidence: 91%
“…The genotyping precision was defined based on the standard deviation of the allele size estimate for each locus. The recommended standard deviation for the equipment is 0.5 base pairs [23], so this value was taken as a reference to define the accuracy of the size estimation in base pairs of each allele.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the increasing research conducted in Peru over the past decade on P. vivax malaria epidemiology,1721 diagnostics,22,23 treatment,12,13,24 vector biology,2528 and molecular genetics,2931 several knowledge gaps still need to be addressed to support the Peruvian NMCP, so that malaria transmission hotspots can be readily identified and that the NMCP can more effectively implement strategies that target such areas with effective interventions 32. In this review, the trends in P. vivax incidence are described in relation to major control efforts implemented in Peru over the past 70 years.…”
Section: Introductionmentioning
confidence: 99%